Significance of Territoriality in Spatial Organization of Coliving Communities: english - Alfirević, Đorđe; srpski, srpski (Arhitektura i urbanizam, 2020)
The issue that the research focuses on is spatial organization of the coliving housing concept and the role that territoriality plays in their typological determination. Past research of coliving concept did not result in a clear systematization of the concept. By comparative analyses of characteristic examples it can be confirmed that in practice, a wide variety of relations between the main functional groups is present (common, shared and individual spaces) and that through links between all of them, different types of the coliving concept are generated. The main thesis of this paper is that the primary parameter, serving as the base of different concepts of coexisting in a shared space, is the “experience of territoriality” i.e. the level of tolerance that space users have in their readiness to share the same space and content with unknown individuals. The main contribution of the paper is the defining of six characteristic types of coliving communities. The importance of this paper is reinforced not only the fact that it initiates the possibility of further theoretical research in the housing sphere, but also in its practical usage in spatial and functional organisation of coliving and cohousing spaces. The presented concepts and classifications can serve as the basis for the definition of new programmes and the design of coliving objects.